Complex GABAB receptor complexes: how to generate multiple functionally distinct units from a single receptor - XU, Chanjuan; Zhang, Wenhua; Rondard, Philippe; Pin, Jean-philippe; Liu, Jianfeng (Frontiers in Pharmacology, 2014)
The main inhibitory neurotransmitter, GABA, acts on both ligand-gated and G protein-coupled receptors, the GABAA/C and GABAB receptors, respectively. The later play important roles in modulating many synapses, both at the pre- and post-synaptic levels, and are then still considered as interesting targets to treat a number of brain diseases, including addiction. For many years, several subtypes of GABAB receptors were expected, but cloning revealed only two genes that work in concert to generate a single type of GABAB receptor composed of two subunits. Here we will show that the signaling complexity of this unit receptor type can be largely increased through various ways, including receptor stoichiometry, subunit isoforms, membrane expression and localization, crosstalk with other receptors or interacting proteins. These recent data revealed how complexity of a receptor unit can be increased, observation that certainly are not unique to the GABAB receptor.